Unknown Old Photos of Karnak Monuments - Romanova, O.O. (Археологія, 2020)
The article introduces a set of photos capturing monuments
and sites of the Karnak Temple Complex (Egypt) in 1907.
These visual documents are held in the archival fond of
D. Shcherbakivsky, in the Scientific Archive of the Institute of
Archaeology, the National Academy of Sciences of Ukraine.
Together with other visual materials, these photos appear to
have been visual illustrations for lecture course on the history
of ancient art by D. Shcherbakivsky. Investigation of the
archival materials and study of the related textual documents
from the Archive give reason to conclude that Ukrainian
ethnographer and anthropologist O. Alesho seems to have been
the author of these photos. He visited Egypt in winter 1907;
Helwan and Luxor were among the sites which he visited,
and the survived photos appear to have been a part of the
photographic recording of his trip. He sent a postcard to his
professor D. Shcherbakivsky with a note from Helwan, this
note attests his trip to Egypt.
At present, the Institute of Archaeology of the NASU has
eight black-and-white photographs capturing sites, objects and
views of Karnak Temple Complex, as they were in 1907. So the
photos of the Institute record one of the earliest known cases
of the photographic recording of the Ancient Egypt sites and
monuments made by Ukrainian scholars. У науковий обіг вводиться невідома раніше серія старих фотографій, на яких зображені пам’ятки та види храмового комплексу Карнаку (Єгипет) в 1907 р. Ці візуальні документи зберігаються в архівному фонді Д. Щербаківського в Науковому архіві Інституту археології НАН України. Схоже, що ці фотографії, поряд із іншими матеріалами
візуального характеру, були ілюстративним матеріалом для курсу лекцій з історії давнього мистецтва Д. Щербаківського. Пошуки архівних матеріалів та вивчення відповідних документів текстового характеру із архіву дають
підставу для висновку, що автором цих фотографій був український антрополог та етнограф О. Алешо, який подорожував Єгиптом взимку 1907 р. Серед інших місць він відвідав Гелуан та Луксор, і досліджувані фотографії,
схоже, є вцілілою частиною тих фотографій, котрі він робив під час своєї подорожі. Свідченням його поїздки до
Єгипту є поштова листівка із повідомленням, яку він відправив своєму вчителю Д. Щербаківському із Гелуану.
Нині Інститут археології НАНУ має вісім чорно-білих фотографій, на яких зображені місця, пам’ятки та види
храмового комплексу Карнаку, такі, якими вони були в 1907 р. Отже, ці фотографії засвідчують один із найбільш
ранніх випадків, коли українські вчені знайомилися й фотографували історичні місця Стародавнього Єгипту. В научный оборот вводится серия фотографий, на которых изображены памятники и виды храмового комплекса
Карнака (Египет) в 1907 г. Эти визуальные документы хранятся в архивном фонде Д. Щербакивского в Научном
архиве Института археологии НАН Украины. Похоже, что эти фотографии вместе с другими визуальными материалами были иллюстративным материалом к лекциям по истории древнего искусства Д. Щербакивского. Поиски архивных материалов и исследования соответствующих документов текстуального характера из архива дают
основания для вывода о том, что автором фотографий был украинский антрополог и этнограф А. Алэшо, который
зимой 1907 г. путешествовал по Египту. Среди мест, которые он посетил, были Хелуан и Луксор, а исследуемые
фотографии, похоже, были сохранившейся частью тех фотографий, которые он делал во время поездки. Свидетельством его поездки в Египет является почтовая карточка с письмом своему учителю Д. Шербакивскому,
отправленная им из Хелуана.
Ныне в Институте археологии НАНУ хранится восемь черно-белых фотографий, на которых запечатлены
места, памятники и виды храмового комплекса Карнака состоянием на 1907 г. Таким образом, эти фотографии
являются свидетельством одного из наиболее ранних случаев, когда украинские ученые знакомились и фотографировали исторические места Древнего Египта.